Jujube Syrup as Natural Sweetener in Jelly Candies: Effects on Texture, Sugar Reduction, and Hydrocolloid Ratios - Lucia Crysanthy Soedirga; Nadia Bianca (Food ScienTech Journal, 2025)
Jelly candies rely on specific gelling agents and sweeteners. This study explores jujube, fruit with underutilized potential as a natural sweetener syrup. Jujube syrup (JS), made by concentrating jujube juice could enhance its value and offer an alternative sweetener for confectionery products like jelly candies. By making jujube into syrup, it can also prolong the shelf life and offer a variety of jujube processing options rather than only dried. Thus, determining the effects of JS: glucose syrup (GS) ratios (100:0, 75:25, 50:50, 25:75, 0:100) and carrageenan (CR): pectin (PT) ratios (1:2, 1:1, 2:1) on jelly candies were investigated. Total sugar (TS), total reducing sugar (TRS), and texture profile analysis (TPA) were measured. Results showed jelly candies made with 100:0 of JS: GS and a 2:1 of CR: PT had the best physicochemical properties. These jelly candies had 42.49±0.76 % of TS, 11.17±0.10 % of TRS, and 0.75±0.00 of water activity. They also displayed texture profile with hardness 190.28±3.31 g, 73.89±4.44 N of gumminess, and 88.65±59.02 Nmm of chewiness. This study demonstrates the potential of JS as a substitute for GS in jelly candies, offering a natural, and potentially lower-sugar alternative. The incorporation of JS not only enhances confectionery formulations but also contributes to healthier product development and the use of sustainable, underutilized raw materials, supporting more responsible and innovative approach in food production.